Successful Photorefractive Keratectomy in a Case of Wilson’s Disease - Saeed Shokoohi-Rad; Hamid-Reza Heidarzadeh (Case Reports in Ophthalmological Medicine)
Purpose. To report a female with a history of Wilson’s disease who underwent a successful photorefractive keratectomy (PRK) for myopic correction. Case Presentation. A twenty-year-old female with a history of Wilson’s disease and D-penicillamine use was referred to our clinic for myopic refractive surgery. Her best-corrected visual acuity (BCVA) was 20/20 for both eyes with a refraction of ‐1.25‐0.5∗75° and ‐1.25‐0.25∗55° for the right and left eyes. The slit examination showed a prominent Kayser-Fleischer ring (K-F ring) in both eyes. She underwent a successful myopic PRK surgery, and her BCVA became 20/20 with no significant refraction. Conclusions. In this report, we report a successful PRK surgery for myopic correction in a case of Wilson’s disease with prominent K-F rings in both eyes.